From Synaptic Protein to Prion: The Long and Controversial Journey of α-Synuclein - Heras-Garvin, Antonio; Stefanova, Nadia (Frontiers in Synaptic Neuroscience, 2020)
Since its discovery 30 years ago, α-synuclein (α-syn) has been one of the most studied proteins in the field of neuroscience. Dozens of groups worldwide have tried to reveal not only its role in the CNS but also in other organs. α-syn has been linked to several processes essential in brain homeostasis such as neurotransmitter release, synaptic function, and plasticity. However, despite the efforts made in this direction, the main function of α-syn is still unknown. Moreover, α-syn became a protein of interest for neurologists and neuroscientists when mutations in its gene were found associated with Parkinson’s disease (PD) and even more when α-syn protein deposits were observed in the brain of PD, dementia with Lewy bodies (DLB), and multiple system atrophy (MSA) patients. At present, the abnormal accumulation of α-syn constitutes one of the pathological hallmarks of these disorders, also referred to as α-synucleinopathies, and it is used for post-mortem diagnostic criteria. Whether α-syn aggregation is cause or consequence of the pathogenic events underlying α-synucleinopathies remains unclear and under discussion. Recently, different in vitro and in vivo studies have shown the ability of pathogenic α-syn to spread between cells, not only within the CNS but also from peripheral locations such as the gut, salivary glands, and through the olfactory network into the CNS, inducing abnormal misfolding of endogenous α-syn and leading to neurodegeneration and motor and cognitive impairment in animal models. Thus, it has been suggested that α-syn should be considered a prion protein. Here we present an update of what we know about α-syn function, aggregation and spreading, and its role in neurodegeneration. We also discuss the rationale and findings supporting the hypothetical prion nature of α-syn, its weaknesses, and future perspectives for research and the development of disease-modifying therapies.